Acute retinal necrosis in a patient with cervical malignant tumor treated with sintilimab: a case report and literature review - Wang, Pei; An, Ming; Zhang, Mengmeng; Yan, Xiaoran; Tong, Nianting (Frontiers in Immunology, 2024)
Acute retinal necrosis (ARN) is an inflammatory disease that is primarily caused by herpesvirus infection, most commonly varicella-zoster virus (VZV), followed by herpes simplex virus (HSV) and occasionally cytomegalovirus (CMV). Sintilimab is an immune checkpoint inhibitor (ICI) that can enhance the body’s anti-tumor immune response. However, treatment with ICIs may lead to reactivation of the VZV. Here, we present a case of ARN caused by VZV infection in a patient receiving sintilimab for cervical cancer. A 64-year-old female patient developed vision loss and floaters with left eye redness for one week after 22 cycles of sintilimab for cervical cancer. Based on clinical manifestations, ophthalmological examination, and vitreous humor biopsy, the patient was diagnosed with acute retinal necrosis syndrome secondary to VZV. After receiving systemic antiviral and anti-inflammatory therapy, retinal necrosis lesions and visual function improved. In conclusion, clinicians should be aware of the risk of ARN when using sintilimab and should actively monitor patients for prompt diagnosis and optimal management of this rare adverse drug reaction.